1998
DOI: 10.1149/1.1838420
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Investigation of the Electrochemical Reduction of Carbonate Electrolyte Solutions at Graphite Electrodes

Abstract: The reductive decomposition of carbonate electrolyte solutions containing lithium ions was studied by differential electrochemical mass spectrometry (DEMS) and subtractively normalized interfacial Fourier transform infrared spectroscopy (SNIFTIRS). The influence of the composition of the negative electrode on its electrochemical behavior was investigated by varying the graphite/binder ratio and using nongraphitic materials. The effect of different electrolyte salts was studied in a 1:1 ethylene carbonate (EC)/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
194
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(202 citation statements)
references
References 1 publication
8
194
0
Order By: Relevance
“…For cells with 0, 0.09, and 0.17 wt% VC, the impedance decreases after the formation cycle, reaching a constant value of ∼5 cm 2 after 20 cycles. In contrast, the LNMO cathode interfacial impedance starts out with a significantly higher value after the first formation cycle (∼22 cm 2 ) for the cells with 0.52 wt% VC and increases with cycle number to ∼30 cm 2 . We believe that the most likely explanation for the LNMO cathode impedance decrease for low VC concentrations is related to the different temperatures during the first formation cycle (25 • C) and the subsequent extended charge/discharge cycling (40…”
Section: Cell Cycling At Elevated Temperatures (40mentioning
confidence: 83%
See 3 more Smart Citations
“…For cells with 0, 0.09, and 0.17 wt% VC, the impedance decreases after the formation cycle, reaching a constant value of ∼5 cm 2 after 20 cycles. In contrast, the LNMO cathode interfacial impedance starts out with a significantly higher value after the first formation cycle (∼22 cm 2 ) for the cells with 0.52 wt% VC and increases with cycle number to ∼30 cm 2 . We believe that the most likely explanation for the LNMO cathode impedance decrease for low VC concentrations is related to the different temperatures during the first formation cycle (25 • C) and the subsequent extended charge/discharge cycling (40…”
Section: Cell Cycling At Elevated Temperatures (40mentioning
confidence: 83%
“…Interfacial resistance of graphite anodes after formation at 25 • C in graphite/LNMO cells (this study) compared to graphite anodes in graphite/LFP cells from our earlier study. 13 The VC concentration is recalculated in units of mg VC /m 2 Graphite to assess for the slightly different areal loadings (namely ∼2.6 mAh/cm 2 geo in the graphite/LNMO cells and ∼2.2 mAh/cm 2 geo in the graphite/LFP cells, based on 340 mAh/g graphite ). The error bars represent the standard deviation between two measurements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Actually, significant evolution of gaseous products such as CO 2 , CO, O 2 , H 2 , CH 4 , C 2 H 4 , C 2 H 6 , C 3 H 6 and C 3 H 8 from the decomposition of carbonate solvents and lithium during battery operation has been detected by various characterization techniques. [14][15][16][17][18][19][20][21] In addition, utilizing isotope analysis, Onuk et al have unambiguously identified the origin of gases evolving in LIBs. 22 Furthermore, by adopting in situ transmission electron microscopy (TEM) 23 and neutron radiography (NR), 9,11 the generation of gaseous bubbles channels formed by the gas have recently been visualized.…”
Section: Introductionmentioning
confidence: 99%